Contribuições para o estudo da pirólise da casca de eucalipto - Rodrigues, Letícia Demuner (2018)
The search for energy sources of renewable, sustainable and low-cost origin has stimulated the development of processes capable of transforming biomass into products that substitute the petroleum derivatives. Pyrolysis is a viable alternative, capable of converting lignocellulosic biomass into solid (coal), liquid (bio-oil) and gaseous products, and the yield of these three products is highly influenced by the type of reactor, biomass characteristics and conditions of the process. The eucalyptus plantation stands out in Brazil and in the world, and its productivity is approximately 6 and 145 million, respectively. With this large production, too much waste is generated: bark, twigs and leaves, and most of these wastes are discarded. Thus, the present work had the objective of studying the pyrolysis of eucalyptus bark, aiming the use of this residue in its industrial application. Initially, some chemical properties were determined in order to characterize the eucalyptus bark used in this work. From the data of thermogravimetry and isoconventional kinetic models, the global activation energy of the pyrolysis reaction of the eucalyptus bark was estimated in: 146.65 kJ.mol-1 (Ozawa), 137.00 kJ.mol-1 (K-A-S), 136.46 kJ.mol-1 (Starink) and 133.02 kJ.mol-1 (Kissinger), being these values similar to those found in the literature. Then, pyrolysis of the eucalyptus bark was carried out in a fixed bed, following an experimental design 32 with two central points, with the response variable being the liquid yield as a function of temperature and particle diameter. The highest yield values of the liquid fraction were in the temperature and intermediate sizes of experiments, 873 K and 1,40mm. In relation to the composition of the bio-oil, the highest percentage is phenolic and acidic compounds, derived from lignin and extractives, respectively.